Few-photon single ionization of cold rubidium in the over-the-barrier regime - Ma, Huanyu; Wang, Xincheng; Zhang, Linxuan; Zou, Zhihan; Yuan, Junyang; Ma, Yixuan; Lv, Rujin; Shen, Zhenjie; Yan, Tianmin; Weidemüller, Matthias; Ye, Difa; Jiang, Yuhai (Physical review, 2023)
Photoionization of rubidium atoms cooled in a magneto-optical trap, characterized by the coexistence of the ground 5S1/2 and excited 5P3/2 states, is investigated experimentally and theoretically with the 400-nm femtosecond laser pulses at intensities of I=(3×109)-(4.5×1012) W/cm2. The recoil-ion momentum distribution (RIMD) of Rb+ exhibits rich ringlike structures and their energies correspond to one-photon ionization of the 5P3/2 state and two-photon and three-photon ionizations of the 5S1/2 state, respectively. With increasing I, the dips near zero momentum (NZM) in the experimental RIMDs become shallow dramatically and their peaked Rb+ momenta ionized from the 5P3/2 state move obviously toward zero while the peaks from the 5S1/2 state do not shift. In addition, the ion-yield ratio of the 5S1/2 state to the 5P3/2 state varies from I to I1.5 as I increases. These features indicate a transition from perturbative ionization to strongly perturbative ionization for the 5P3/2 state. Numerical simulations by solving the time-dependent Schrödinger equation (TDSE) can qualitatively explain the measurements of the RIMD, photoion angular distributions, and ion-yield ratio. However, some discrepancies still exist, especially for the NZM dip, which could stem from the electron-electron correlation that is neglected in the present TDSE simulations since we have adopted the single-active-electron approximation.
Gesehen am 13.06.2023